Analysis of Obstacles And Quality Education Strategies at MI NW Nurul Haramain Narmada - Siti Alfiyana Rahmatillah; Muhammad Amin Nur; Nurhandayani Hasanah (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
The quality of education needs to be continually improved to enhance the quality of educational institutions and schools. Several strategies are required to enhance the quality of an institution, and the leadership of the school principal also plays a significant role. The research objective is to identify the causes and strategies for the quality of education at MI NW Nurul Haramain Narmada. The method used is a qualitative descriptive method. The research results indicate that there are obstacles and improvements made by MI NW Nurul Haramain. The obstacles faced include not all items in the EDM being adequately filled; there are several indicators that still have low values, which are noted by the school. Improvements at MI NW Nurul Haramain Narmada include activities such as memorization (tahfidz), calligraphy, futsal, math and science, music, Arabic, English, and Scouts. Therefore, it can be concluded that MI NW Nurul Haramain Narmada shows significant improvement.